Appraisal and rewards systems for virtual project management teams and the challenges for human resource management. (2nd March 2012) - Mitlacher, Lars W.
Virtual teams and virtual project management teams in particular have become more widespread with the rise and distribution of new technology and the increasing use of the internet. As companies deploy virtual teams to guarantee a seamless work on different projects, the question arises how the performance of virtual teams should be measured and how the performance should be rewarded. Using a strategic human resource management framework, the paper develops several propositions on the design of appraisal and rewards systems for virtual project management teams. The aim of the analysis is to shed light on the question what challenges arise by measuring the performance of teams, how to possibly resolve them, how to design an adequate rewards system for virtual project management teams and what are the consequences for company performance.